Concepciones de los estudiantes de décimo grado de la Institución Educativa Liceo del Llano sobre los factores que inciden en su aprendizaje del idioma inglés (2019)
This mixed, qualitative - quantitative study seeks to uncover and analyze the conceptions of the students of the Liceo Del Llano School, in the Municipality of Arauquita, Arauca, Colombia, about their learning of English as a foreign language and the teaching they receive. From this analysis, the study also aims to reveal the motivations that these students have towards this learning. Data collection was achieved through a Likert-scale survey and a semi structured interview. The study concludes that students give great importance to the learning of the English language because it allows them several possibilities of advancement in their lives; however, the classes they receive are not attractive enough to maintain their attention and improve their performance. I hope to contribute with this study to the possibility that teachers in this remote municipality of the country, and probably others who are in similar geographical conditions and where the study of a foreign language has little real use, rethink our pedagogical practices in favor of the students.